Pola Asuh Anak Oleh Orang Tua Tunggal dalam Pembentukan Karakter Anak - Elsa Sepriyani; Anak Agung Ngurah Anom Kumbara; Ida Bagus Gde Pujaastawa (Department of Anthropology Udayana University, 2019)
Parenting is a process to improve and support the child's development in shaping the child's character. In general, parents want their children to have noble character, character and always healthy, parents have a role in shaping the personality and self-discipline of a child, but vice versa in incomplete families or single parents. In Malacca Village there are relatively many single parents in caring for their children. The research aims to find out: (a) What is the role of single parents in the formation of children's character in Malacca Village and (b) What are the implications of the role of single parents in the formation of children's characters in Malacca Village. This research uses the basic structural personality theory and socialization theory. Ethnographic research models with qualitative research types, including data collection techniques through observation, interviews, literature studies, and data analysis to process field findings. The results showed that the phenomenon of parenting single parents in the formation of children's character in the Malacca Village there are three forms of parenting namely democratic parenting, authoritarian parenting, and permissive parenting, this is due to factors namely, values ??and norms, pattern processes foster care, the role of a large family in caring for children of single parents, a form of parenting. The implications are educational factors, religious factors, social relations factors.